Determination of GL‐V9, a derivative of wogonin, in rat plasma by UPLC–MS/MS and its application to a pharmacokinetic study after oral and pulmonary administration. (22nd May 2019) - Xing, Han; Ren, Chang; Kong, Ying; Ni, Qi; Wang, Zeyu; Zhao, Di; Li, Ning; Chen, Xijing; Lu, Yang
Abstract: GL‐V9, a derivative of wogonin, shows much more potent anticancer properties than wogonin. In this study, a selective, sensitive and rapid ultra‐high‐performance liquid chromatography tandem mass spectrometry (UPLC–MS/MS) method was developed and validated for the determination of GL‐V9 in rat plasma. Plasma samples were processed using methanol to precipitate protein. Chromatographic separation of analytes was achieved on a C18 column using gradient elution within 4.5 min. The mobile phase consisted of acetonitrile and water including 0.1% ( v /v) formic acid and 5 mm ammonium acetate. GL‐V9 and caffeine (internal standard) were monitored by positive electrospray triple quadrupole mass spectrometer and quantified using multiple reaction monitoring (MRM) mode with the transitions of m / z 410.20 → 126.10 (GL‐V9) and 195.10 → 138.00 (IS: caffeine), respectively. Good linearity was obtained over the range of 2–1000 ng/mL ( R 2 > 0.99) and the extraction recovery was 101.91 ± 11.34%. The intra‐ and inter‐day precision variations were small (RSD 1.35–6.96%) and the relative error (RE) of accuracy was −7.35–6.27%. The established and validated UPLC–MS/MS method was successfully applied to study the pharmacokinetic behavior of GL‐V9 after administration through different delivery routes. The results demonstrated that pulmonary delivery exhibited a greater advantage in terms of improving bioavailability compared with oral administration.